The Contribution of Industrial Point Emissions on Air Pollution: A Case Study for Kayseri Province - Zeynep İpek; İbrahim Uyanık (Doğal Afetler ve Çevre Dergisi)
In this study, the contribution of power plants belonging to industrial power generation facilities in Kayseri City Center to air pollution was investigated. For this reason, in the five-year period between 2015-2019 in Kayseri Province, besides the natural gas used in the industry, the emission amounts have been revealed with the data obtained from the power plants that use coal for industrial energy supply. The contributions of these sources to air pollution are also evaluated on an annual basis with the data of the National Air Quality Monitoring Network. In addition, the relationship between emission amounts and pollutant concentrations on an annual basis was examined using the Pearson correlation. The emission amounts calculated for the total PM (particulate matter), SO2 and NOx parameters during the five-year period, 2015-2019, are 1,540 tons, 500 tons and 10,328 tons, respectively. As a result of the emission amounts (tons/year) calculated for the PM, SO2 and NOx parameters, the emission rates of the three pollutants are 14%, 4% and 82%, respectively. When the contribution of coal used in power plants in industries and natural gas used in industry to air pollution in Kayseri is compared, it is seen that coal makes the highest contribution with 89% of PM 97% of SO2 and 62% of NOx. It was concluded that the decrease in PM10 concentrations and the increase in NOx concentrations from 2015 to 2019 may be associated with the increase in natural gas use in the city. The use of industrial natural gas and coal could not be associated with the change in SO2 concentrations. It has been found that the NOx emission amounts originating from the use of coal for energy production in industrial facilities have a high correlation with the NOx concentration. In future studies, the contribution of each point source to air pollution can be determined by determining the use of domestic coal and natural gas.